An Evidence-Based Approach to Utilizing Cold Therapies for Post-Exercise Recovery - Adam Grainger; James J. Malone; Joseph T. Costello; Chris M. Bleakley; Robert Allan (Physiologia)
Whilst cold therapies such as cold-water immersion are regularly used in practice, the practical application does not always align with best practices. In this commentary, we highlight the key components of the British Association of Sport and Exercise Sciences (BASES) Expert Statement on the use of cooling therapies for post-exercise recovery and provide additional discussion on the empirical evidence and rationale that informed our perspective. We developed a series of specific questions to ensure that cold therapy recovery protocols are context-specific and tailored to the needs of the individual athletes. These questions, which cover the WHEN, WHAT, and HOW of cold therapy, were central to the development of the Expert Statement. This was presented as a decision tree to ensure that key messages could be concisely disseminated across a range of sporting environments and populations (e.g., gyms, locker rooms, and treatment rooms), supporting and informing decision-making for those wanting to use cold therapy to assist their recovery in line with previously published peer-reviewed work. Discussion points included the suitability of cooling therapies in some contexts, how athletes’ choice of cooling mode should be largely driven by practicalities (e.g., budget and availability), and, lastly, future research directions.